Phase transition and thermal depolarization of double perovskite modified low sintering temperature PbTiO3 piezoelectric ceramics. Issue 3 (February 2016) - Huang, Haining; An, Zhao; Huang, Pangfeng; Li, Dan; Liao, Qingwei
Abstract: Phase transition and thermal depolarization of PbTiO3 piezoelectric ceramics with Double Perovskite modified were investigated. With 5 mol% Double Perovskite (BFM, BNM, YNM, SNM), the PbTiO3 has a possibility to change the crystal structure to a large extent, and the sintering temperature can be controlled below 960 °C. With increasing ionic radius difference between addition and PbTiO3, the crystal structure of modified PbTiO3, measured by synchrotron radiation changed from Tetragonal (P4 mm) to Orthorhombic (Pmm2) and became more ordered (from 2 × 2 × 1 super cell to 6 × 2 × 2 super cell). The ordered Orthorhombic structure PT has higher phase transition temperature (496–540 °C) than the Tetragonal PT (481 °C). All modified PbTiO3 ceramics show high depolarization temperature. The depolarization temperatures of PT-BFM, PT-BNM, PT-YNM, and PT-SNM are 470 °C, 480 °C, 495 °C, and 505 °C, respectively.